The immediate impact of the 2019 novel coronavirus (COVID-19) outbreak on subjective sleep status - Lin, Li-yu; Wang, Jie; Ou-yang, Xiao-yong; Miao, Qing; Chen, Rui; Liang, Feng-xia; Zhang, Yang-pu; Tang, Qing; Wang, Ting (Sleep medicine, 2021)
An outbreak of the 2019 novel coronavirus (COVID-19) has been ongoing in China since January 2020. The threat of infection affects the work and life of most of the population and may also damage sleep. This study aims to examine the subjective sleep status and mental health of the population during the peak of the COVID-19 epidemic. The data were collected through an online questionnaire with a sample of 5461 individuals in China from February 5, 2020, to February 23, 2020. Participants were divided into four groups based on their degree of threat from COVID-19: Group 1 was most closely associated with COVID-19, including inpatients diagnosed with COVID-19, first-line hospital workers and first-line management staff; Group 2 included outpatients diagnosed with COVID-19 and patients who developed a fever and visited the hospital; Group 3 included people related to Group 1 or 2, such as their colleagues, relatives, friends and rescuers; and Group 4 was the farthest removed from contact with COVID-19, covering the general public affected by COVID-19 prevention strategies. The Insomnia Severity Index (ISI), Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder Scale (GAD-7) and Acute Stress Disorder Scale (ASDS) were used. Threat degree of COVID-19 (groups) had significant correlations with insomnia, depression, anxiety, and stress (p < 0.05, p < 0.01). Age, gender, and area (Hubei province or other provinces) had significant correlations with insomnia (p < 0.01). A total of 1380 (24.46%) participants were suspected of having major depression based on the PHQ-9. Additionally, 1042 (18.47%) participants were suspected of having generalized anxiety disorder based on the GAD-7. A total of 892 (15.8%) of the participants had Acute Stress Disorder (ASD) according to the ASDS. The prevalence of clinical insomnia during the outbreak was 20.05% (1131) according to the ISI. The factors of satisfaction with the current sleep pattern and how perceptible the symptoms of the current sleep pattern are to other people (p < 0.05) and the middle (difficulty staying asleep) and terminal (waking up too early) (p < 0.01) factors of the ISI were significantly different across groups. A total of 1129 (20.01%) participants spent more than one hour awake in bed. The results indicated that insomnia is more severe in people who are female, young, living in the epicenter and experiencing a high degree of threat from COVID-19. As prevention and treatment efforts continue with regard to COVID-19, the general public has developed poor sleep hygiene habits, which deserve attention. •It reported the immediate impact of sleep status of a large sample at the peak of the COVID-19 spread in China.•Reports on sleep habits of individuals in China by different degrees of COVID-19 threat.•The threat degree of COVID-19 is associated with the prevalence of anxiety, depression and acute stress disorder.•The general public has developed poor sleep hygiene habits which deserve attention.